Estudio de mercado para la creación de productos turísticos en los humedales de la provincia de Manabí - Cevallos Ramírez, Tulio Urbano (2021)
The proposed research was developed in three recognized wetlands of Manabí: Machalilla National Park (Puerto López), Isla Corazón Y Fragatas Wildlife Refuge (Bahía de Caráquez) and La Segua Wetland (Chone); The same purpose is to carry out a market study that promotes the development of tourism products in these ecosystems. For this purpose, a general diagnosis of the wetlands was carried out, managing to determine their tourism potential through field visits and information gathering. Likewise, bibliographic sources were analyzed and interviews were applied to community members to obtain more information on the areas. Next, supply and demand were analyzed, using the potentialities matrix, in order to characterize the resources of each wetland. To study the competition, the competitive profile matrix and the tourist registry of each site were used. Based on the information collected and in correspondence with the results of the market study, it was possible to design a tourism product for each wetland, which includes: tourist attractions, itineraries, services offered and travel costs; with the aim of providing tourists with an innovative and low-cost product. As a result, it is evident that Manabí has a great tourist potential made up of 370 tourist attractions; In addition, the need to update the inventory of resources in the province is confirmed; since, currently, it is not known exactly what are the natural and cultural attractions that Manabí has.